Tacit Knowledge Sharing di Sekolah Islam: Analisis Kepemimpinan dan Iklim Keamanan Psikologis - Dewiana Novitasari; Masduki Asbari; Firdaus Putra; Dwi Ferdiyatmoko Cahya Kumoro; Muhamad Agung Ali Fikri (Jayapangus Press, 2021)
This study aims to examine the effect of charismatic leadership on the psychological safety climate and tacit knowledge sharing. This study also investigates the central role of psychological safety climate as a mediating variable between charismatic leadership and tacit knowledge sharing. This study adopted a simple random sampling method with 63 samples of teachers from a Madrasah Tsanawiyah in Banten. The results of this study indicate that charismatic leadership has a significant direct influence on the climate of psychological security and tacit knowledge sharing. Likewise, the psychological security climate has a significant direct influence on tacit knowledge sharing. This study also finds evidence that charismatic leadership has a significant indirect effect on tacit knowledge sharing through the mediation of a psychological security climate. Thus, the psychological safety climate acts as a partial mediator in this research model.